Analisis Gender Dalam Program Nasional Penanggulanagan Kemiskinan Berbasis Pemberdayaan Masyarakat Di Desa Kurau Bangka Tengah - Utami, Atikah Dewi (Scientia: Jurnal Hasil Penelitian, 2023)
Gender Equality and Justice (KKG) with the main aim of increasing community participation, especially poor communities and women's groups. This research aims to analyze access and control of poverty alleviation programs in Kurau Village. Gender equality and justice, which is one of the development goals set out in the 2005-2025 RPJPN and outlined in the 2015-2019 RPJMN, is faced with three strategic issues, including increasing the quality of life and the role of women in development. This research uses quantitative methods with respondents in this research as many as 60 households divided into 30 men and 30 women with the unit of analysis in this research being individual households. The Spearman Rank correlation test is used to prove hypotheses in research with descriptive analysis referring to theory, observation results and in-depth interviews. The research results show that only income level and education level are significantly related to the level of access to program components. Furthermore, the level of income is negatively related to the level of control over program components at the level α= 0.20 to α= 0.30. Keywords: Gender Equality, Access, Control